Employing workplace-based assessment as a tool to facilitate learning by strengthening the feedback component - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Tabriz University of Medical Sciences, 2021)
Workplace-based assessments (WPBA) have been recommended in both undergraduate and postgraduate courses. WPBA tools assess the "does" level in Miller's framework for assessing clinical competence. In this perspective, we focus on the rationale for and effective use of WPBA tools as part of formative assessment and feedback for learners. WPBA tools are an effective approach to facilitate learning because they ensure that the content of the training program, the intended competencies, and the assessment align with each other. The learning during the use of WPBA occurs via feedback offered to students; it predominantly informs the students about their progress and the areas in which more focus is required. Moreover, the feedback plays an important role in motivating students to continue learning and advises them on how their learning can be expedited, including the use of appropriate resources. In conclusion, workplace-based assessment tools in medical training should be used not only to conduct an authentic assessment but to also facilitate learning among students. The process of learning is facilitated by giving timely feedback in alignment with the students' needs, and all faculty members should be encouraged to use the opportunity of assessment for the benefit of students.